PENGARUH DARI WHOLESOME – SCATTERING – GAME PADA KEMAMPUAN SISWA KELAS X SMAN 12 PEKANBARU DALAM MENULIS TEKS DESKRIPTIF - sartika, Mira; ', Dra. Atni Prawati, M.Ed; ', Erni, S.Pd, M.Hum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a pre-experimental research conducted by using a pre-test – treatment – post-test design which used one group pretest-posttest design. The objectives of this research is to find out whether wholesome scattering game is effective to improve the ability of the first year students of SMAN 12 Pekanbaru in the Academic Year 2016/2017 in writing descriptive text. The population of this research was 372 of the First Year Students of SMAN 12 Pekanbaru and cluster sampling method was used to select one class of students to become the sample. As a result, X MIPA 5 of SMAN 12 Pekanbaru which is total number of the students of class is 35 students were chosen as the sample. The data of this research were collected by giving the writing test about descriptive text (pretest-posttest) to the students. Data were analyzed by using t-test formula. The results of data analysis showed the mean score of pretest was 52.57 and the mean score of posttest was 66.16. From the results of data analysis, it can be concluded that there is significant difference between pre-test and post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this research was accepted and null hypothesis was rejected. It also meant that, wholesome scattering game is a technique for teaching that gave a good effect on the ability of the first year students of SMA Negeri 12 Pekanbaru in writing descriptive texts.